Coating with both anti-icing and photothermal conversion properties and preparation method thereof
By using phase -changing micro -capsules and bipolar micro -capsules with phase -changing materials in the paint, combined with the reaction of dopamine and carboxyl beetine acrylamide to form super -water coatings, solving the high cost of anti -coverage in the existing technology The problem of low efficiency and insufficient wear resistance achieves efficient and economic anti -coverage effects, and has the ability to transform light thermal conversion.
Patent Information
- Application Number
- CN202410751153.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-12
AI Technical Summary
The prior art has problems such as high cost, low energy efficiency, and environmental pollution in preventing ice coating, and superhydrophobic and superhydrophilic ice coating surfaces have shortcomings in long-term effectiveness, wear resistance and medium resistance.
Phase micro -capsules that are covered with phase -changing materials are used to form a double -shell micro -capsule through dopamine, carboxyl beetine acrylamide, copper sulfate, and hydrogen peroxide, and placed it in polyethylene pyrigone aquatic solution to form a kind of Premier water coatings that are transformed by anti -cover ice and light heat.
This coating can significantly delay the freezing time under low temperature conditions, reduce the adhesion of ice and surface, and automatically fall off with the effect of wind and its own gravity, achieve efficient anti -overwing effect, and also have the ability to transform light thermal conversion capacity Essence
Smart Images

Figure CN118546586B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coating having both anti-icing and light-to-heat conversion functions and a preparation method thereof. Background Art
[0002] Most areas south of the Huaihe River in my country often encounter "freezing rain" (low temperature rain, snow and ice), which leads to serious icing problems in the power, energy, and communications engineering fields. Moreover, once the railway locomotive speed radar is covered with ice, its wave transmission performance is sharply reduced, forcing the train to downgrade and reduce speed, which is simply worse for the railway department's heavy transportation operations in winter. Therefore, how to deal with and reduce surface icing has become a severe challenge faced by many engineering fields.
[0003] In order to delay the ice formation problem, researchers at home and abroad have successively proposed two types of methods to prevent surface ice accumulation: active and passive. Active anti-icing methods are mostly based on the idea of deicing and ice melting, and are mainly based on active deicing methods such as electricity, machinery and chemical solvents. However, this method generally has problems such as high cost, low energy efficiency, waste of energy and even environmental damage. Passive anti-icing methods aim to inhibit or delay the formation of ice crystals on the surface of the material, reduce the adhesion of ice crystals to the substrate, and have the advantages of low energy consumption, environmental friendliness and wide application range. At present, it has become the preferred method for anti-icing, among which the research on super-hydrophobic anti-icing surface and super-hydrophilic anti-icing surface is the most typical. Super-hydrophobic anti-icing technology uses the bionic principle of lotus leaves to prepare micro-nano structures on the surface to form a self-cleaning super-hydrophobic interface coating. The theoretical anti-icing effect is significant, and its potential effects include three aspects: ① Water droplets on the super-hydrophobic surface are easy to roll and slide under the action of natural external forces, thereby greatly reducing the amount of water hanging before freezing; ② Inhibit or delay the formation of ice crystals on the surface of the material; ③ Reduce the adhesion of ice crystals to the contact interface. There are currently two preparation methods for super-hydrophobic anti-icing surfaces: multi-step method and one-step method. The multi-step method generally uses etching and physical vapor deposition. Both etching and vapor deposition methods can obtain super-hydrophobic surfaces with excellent performance, but the preparation process needs to be carried out under vacuum, and has high requirements on the size and structure of the substrate and parts, making it difficult to apply in actual engineering. Later, it was changed to sol-gel method, but its preparation process is still relatively complicated, which greatly limits its practical engineering application and promotion. Subsequently, a one-step method was developed, that is, in the film formation process, multiphases are generated by controlling conditions to form a micro-nano double-textured surface roughness. The water contact angle (Water contact angle, WCA) of the prepared coating is >166°, and the water sliding angle (Water sliding angle, WSA) is <5°. This one-step film formation method is relatively simple to prepare self-cleaning surfaces, and the substrate, size, and shape of the sample are not restricted, showing good engineering applicability. Since the super-hydrophilic anti-icing surface has a large number of hydrophilic groups, the contact angle of the droplet on the solid surface is less than 10°. It can absorb non-freezable water first through hydrogen bonding, solvation or electrostatic interaction with water molecules, and quickly spread on the surface to form a highly dense hydration layer. When the droplet freezes on the surface, the hydration layer can act as a lubricant between the ice and the substrate surface, thereby reducing the adhesion between the ice and the surface, so that the ice automatically falls off the surface under the influence of wind and its own gravity, thereby achieving the effect of repelling ice. At present, the most studied organic materials for constructing super-hydrophilic surfaces are polyethylene glycol (PEG) and zwitterionic polymers. Inorganic materials are intrinsically hydrophilic materials represented by SiO2 and graphene oxide and photosensitive materials represented by TiO2 and ZnO. The use conditions of these materials are harsh and they become super-hydrophilic only when exposed to ultraviolet conditions.
[0004] It can be seen from the above solution that the use of surface super-hydrophobicity to prevent ice coating affects the long-term anti-icing ability due to the unevenness and fragility of its surface micro-nano dual structure, so the orderliness and controllability of the micro-nano dual structure on the surface are still to be studied in depth. In addition, the super-hydrophobic structure prepared by the multi-step method cannot be applied in large-scale engineering due to the harsh preparation method, and the self-cleaning super-hydrophobic coating prepared by the one-step method also has short timeliness, is not wear-resistant, and is not weather-resistant and medium-resistant. The ability is also insufficient, which limits the large-scale and extensive engineering application of the self-cleaning super-hydrophobic coating. The latest research shows that hydrophilic polymers containing a large number of hydrophilic groups, such as zwitterionic polymers, have strong hygroscopicity and can preferentially absorb non-freezable water in the air to alleviate the problem of substrate surface ice coating, but when large-scale ice accumulation occurs, the super-hydrophilic coating surface will still be covered with ice, so how to quickly eliminate the influence of ice accumulation on the anti-icing of super-hydrophilic coating still needs to be studied in depth. Summary of the invention
[0005] In order to reduce the impact of icing on equipment, the present application first proposes a method for preparing a coating having both anti-icing and photothermal conversion properties, which comprises the following steps:
[0006] (1) uniformly dispersing phase change microcapsules coated with phase change materials in a Tris-HCl buffer solution to form a capsule buffer solution;
[0007] (2) adding dopamine, carboxybetaine acrylamide, copper sulfate and hydrogen peroxide to the capsule buffer, stirring and reacting, and after the reaction is completed, filtering, washing and drying to obtain double-shell microcapsules;
[0008] (3) The double-shell microcapsules are placed in a polyvinyl pyrrolidone aqueous solution containing an anti-settling agent and a defoaming agent to form a coating.
[0009] The objective of the present application is to prepare a super-hydrophilic coating. After the super-hydrophilic coating is formed, the coating surface has a strong interaction force with water, and water droplets can be completely spread out on the coating surface in an instant to form a water film. Therefore, during use, these coatings can first absorb non-freezable water in the air, quickly spread out on the coating surface and form a highly dense hydration layer. When the droplets freeze on the coating surface, the hydration layer can act as a lubricant between the ice and the coating surface, thereby reducing the adhesion between the ice and the coating, so that the ice automatically falls off from the coating surface under the action of wind and its own gravity, thereby achieving an ice-repellent effect.
[0010] In the present application, dopamine (DA) is induced by CuSO4 / H2O2 to initiate co-deposition of carboxybetaine acrylamide (CBAA) on the surface of phase change microcapsules to form double-shell microcapsules. During the co-deposition process, DA has the functions of both a monomer initiator and an adhesion site. The quinone DA is generated by DA oxidation self-polymerization as an initiator, which successfully initiates the polymerization of CBAA monomers and co-deposits them on the surface of phase change microcapsules to form a super-hydrophilic surface with strong anti-fouling properties.
[0011] The present invention adopts CuSO4 / H2O2 composite oxidant to oxidize DA to increase the oxidative self-polymerization rate of DA. If O2 in air is used alone as an oxidant, the reaction needs to last for more than 60 minutes. However, adding H2O2 alone does not promote the self-polymerization of DA, which is not much different from air oxidation. When CuSO4 / H2O2 composite oxidant is used, Cu 2+ The oxidizing property of Cu 2+ and H2O2 to produce active oxygen free radicals, such as superoxide anion (O2·-), hydrogen superoxide (HO2·) and hydroxyl radical (OH·). These free radicals can significantly increase the self-polymerization of DA and the deposition rate of its polymer PDA coating, so that the CuSO4 / H2O2 composite oxidant can turn the color of the DA solution into dark black within 5-10 minutes.
[0012] CBAA is polymerized into polyacrylamide carboxybetaine (PCBAA). The hydrophilic groups contained in the zwitterionic polymer PCBAA can interact strongly with water molecules, so that the formed hydration layer can still exist stably at low temperatures. The hydration layer can act as a lubricant between the ice and the coating surface, thereby reducing the adhesion between the ice and the coating surface. The hydrophilic groups such as carboxyl and amide groups contained in PCBAA interact with water molecules stronger than hydrogen bonds.
[0013] In addition, since phase change microcapsules with phase change materials are used to prepare double-shell microcapsules, the phase change materials therein are used to enhance the overall thermal insulation and heat storage properties of the coating surface to improve the anti-icing performance of the coating at low temperatures.
[0014] In general, this application utilizes the synergistic effect of the excellent binding ability of PCBAA zwitterionic polymer with non-freezing water, the thermal energy storage of phase change materials, and the photothermal conversion effect of PDA to maximize the anti-icing effect of the surface and effectively slow down the occurrence of surface ice accumulation. When the coating in this application forms a coating, the water droplet contact angle on the coating surface can reach 7.8°, and the freezing delay time at -18°C is 190.3s, which is 127.3s longer than that of pure PVP coating.
[0015] Specifically, in order to prevent the formed double-shell microcapsules from sticking together during the reaction, the pH of the Tris-HCl buffer solution is 8-8.8, and the concentration of the phase change microcapsules in the Tris-HCl buffer solution is 5-10 g / L.
[0016] Specifically, in step (2), the mass ratio of phase change microcapsules, dopamine (DA), carboxybetaine acrylamide (CBAA), copper sulfate and hydrogen peroxide is (3.5-5.5):1:(8-15):(3-6):(3-4), wherein hydrogen peroxide is calculated as pure H2O2. Under the above conditions, an outer shell can be formed again on the outside of the phase change microcapsule. When the amount of CBAA is low, the polymer brush formed on the single-shell microcapsule is low, resulting in a larger contact angle on the coating surface; when the amount of CBAA is high, the intramolecular dipole-dipole interaction between CBAA monomers leads to self-association, and the brush layer is in a super-collapsed state. In this super-collapsed state, the polyzwitterionic layer contains much less water than the non-associated state, which also results in a larger contact angle on the coating surface.
[0017] Furthermore, in order to ensure smooth reaction, in step (2), the reaction temperature is 20-30°C, the reaction time is 0.8-2.5h, and the stirring speed is 150-300r / min.
[0018] Specifically, in order to have appropriate viscosity and concentration for easy brushing and to make the formed coating have the best anti-icing performance, in step (3), the mass ratio of double-shell microcapsules to polyvinyl pyrrolidone is 1:(8-15), the concentration of polyvinyl pyrrolidone aqueous solution is 8-13wt%; the polyvinyl pyrrolidone aqueous solution contains 0.5-2wt% of anti-settling agent and 0.1-0.5wt% of defoaming agent, wherein the anti-settling agent is fumed silica and the defoaming agent is an aqueous silicone defoaming agent. Polyvinyl pyrrolidone refers to polyvinyl pyrrolidone in polyvinyl pyrrolidone aqueous solution. In the above ratio, the double-shell microcapsules and polyvinyl pyrrolidone have good film-forming properties and a small contact angle. When the content of the double-shell microcapsules is too low, the hygroscopicity of the coating is poor and it is unable to lock in sufficient moisture and form a lubricating layer. When the content of the double-shell microcapsules is too high, it will lead to excessive absorption of moisture, so that the coating is always wet at room temperature and has strong viscosity, thereby affecting the film-forming property of polyvinyl pyrrolidone and making the coating lose its use value.
[0019] Specifically, the phase change microcapsules are prepared by the following steps:
[0020] (1.1) Hexadecyltrimethylammonium bromide (CTAB) is dissolved in an ethanol-water solution and stirred to form a water phase; n-hexadecane (n-HD) and tetraethyl orthosilicate (TEOS) are mixed and stirred to form an oil phase;
[0021] (1.2) Mixing the above-mentioned water phase and oil phase, stirring, emulsifying, and forming an oil-in-water solution; preferably using a disperser homogenizer, the stirring speed is controlled at 8000-11000r / min, the time is 5-10min, and then ultrasonically treating for 5-10min, to obtain a stable oil-in-water solution;
[0022] (1.3) Adding ammonia water to the oil-in-water solution to make the pH of the solution reach 8.8-9.2, keeping stirring, reacting, filtering after the reaction is completed, washing and drying the product to obtain phase change microcapsules; during the reaction, the stirring speed is controlled at 800-1000r / min, preferably washing with ethanol aqueous solution, the drying temperature is controlled at 40-60°C, and the drying time is controlled at 20-30h. There is no strict restriction on the concentration of ammonia water, and ammonia water of conventional concentration can be used. The present application specifically uses ammonia water with a concentration of 15-18wt%.
[0023] The phase-change microcapsules formed in this application are energy storage capsules with SiO2 as the shell and n-hexadecane as the phase-change material. SiO2 is not only a photosensitive material, but also a hydrophilic material, but it only becomes super-hydrophilic when exposed to ultraviolet light. Since the surface of SiO2 has a large number of hydroxyl groups, it becomes a super-hydrophilic material, which can improve the hydrophilic properties of the coating. The surface of the phase-change microcapsules prepared in this application is regular spherical and crack-free, and the content of the phase-change material in the phase-change microcapsules is as high as 78.8wt%.
[0024] Specifically, the mass ratio of n-hexadecane to tetraethyl orthosilicate is 10:(4-7). The greater the content of phase change material in the capsule, the greater the latent heat released by the phase change material during the phase change. The appropriate core-shell ratio can not only ensure the maximum encapsulation of the phase change material, but also ensure the integrity of the shell and avoid leakage of the phase change material. When the proportion of tetraethyl orthosilicate is too high, the proportion of the shell will increase, resulting in a decrease in the content of the phase change material; and when the proportion of tetraethyl orthosilicate is too low, the shell will break, resulting in leakage of the phase change material, and a good phase change material cannot be formed. The mass ratio of n-hexadecane to tetraethyl orthosilicate is preferably 10:(4-6), and more preferably 10:(4.5-5.5).
[0025] Specifically, the mass ratio of the oil phase to the water in the ethanol aqueous solution is 1:(9-11), the mass ratio of cetyltrimethylammonium bromide (CTAB) to the ethanol aqueous solution is 1:(80-90), and the volume ratio of ethanol to water in the ethanol aqueous solution is 1:(2-3).
[0026] CTAB is a surfactant to separate the formed capsules. Under the above ratio, the separation effect of CTAB on phase change microcapsules can be fully exerted. Tetraethyl orthosilicate (TEOS) uses water as a solvent for hydrolysis reaction, but TEOS is difficult to dissolve in water at room temperature. This application uses ethanol as a solubilizer for TEOS, taking into account both economic costs and environmental protection effects. Under appropriate water-to-oil ratio conditions, TEOS can fully undergo hydrolysis reaction. In the ratio of water in the oil phase to the ethanol-water solution, when the proportion of water is too low, the hydrolysis reaction of TEOS will be affected. When the proportion of water is too high, the concentration of monosilicic acid generated by TEOS during the hydrolysis reaction will be diluted, and the silicon-oxygen bonds generated by monosilicic acid during the condensation reaction will also be re-hydrolyzed.
[0027] Specifically, in order to make the reaction proceed smoothly, in step (1.3), the reaction time is 20-30h and the reaction temperature is 30-40°C.
[0028] Secondly, the present application also discloses a coating having both anti-icing and photothermal conversion properties, which is prepared using any of the preparation methods described above.
[0029] The photothermal conversion effect and thermal energy storage capacity based on phase change microcapsules proposed in the present invention, combined with the synergistic effect of the outstanding surface superhydrophilic wettability of zwitterionic polymers, can not only effectively solve the impact of ice accumulation on the anti-icing of superhydrophilic coatings, but also explore the interaction principle, freezing mechanism and behavior of superhydrophilic coatings combined with non-freezable water and freezable water in water, thereby scientifically guiding people to achieve winter anti-icing and avoid losses caused by icing disasters. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM image of 1# phase change microcapsule.
[0031] Figure 2 It is the infrared spectra of n-HD, SiO2 and 1# phase change microcapsule.
[0032] Figure 3 These are SEM images of 1# phase change microcapsule, 1# double-shell microcapsule and 4# double-shell microcapsule.
[0033] Figure 4 It is the infrared spectra of 1# phase change microcapsule, 1# double-shell microcapsule and 4# double-shell microcapsule.
[0034] Figure 5 These are the XPS pictures of 1# double-shell microcapsule and 4# double-shell microcapsule.
[0035] Figure 6 It is a curve diagram of the temperature-time change of microcapsules.
[0036] Figure 7This is the actual appearance picture of the anti-icing detector. DETAILED DESCRIPTION
[0037] Example 1
[0038] The preparation steps of 1# phase change microcapsules are as follows:
[0039] (1.1) 1.5 g of hexadecyltrimethylammonium bromide (CTAB) was dissolved in 124 g of ethanol-water solution and stirred to form an aqueous phase; 6 g of n-hexadecane (n-HD) and 3 g of tetraethyl orthosilicate (TEOS) were mixed and stirred to form an oil phase; the ethanol-water solution was prepared by mixing 34 g of CTAB and 90 g of distilled water, and the volume ratio of ethanol to water was 1:2.09.
[0040] (1.2) After the water phase and the oil phase are mixed, a dispersion homogenizer is used to homogenize and stir at a stirring speed of 10000 r / min for 5 minutes, and then ultrasonically treated for 5 minutes to complete emulsification to form an oil-in-water solution;
[0041] (1.3) Add 25 wt% ammonia water to the oil-in-water solution to make the pH of the solution reach 8.8-8.9, keep stirring, stir at 800 r / min in a 30°C water bath, and react for 30 hours. After the reaction is completed, filter and wash the product with a 1:1 ethanol aqueous solution, and then dry at 50°C for 24 hours to obtain 1# phase change microcapsules. Figure 1 This is the SEM image of 1# phase change microcapsule. The surface of the phase change microcapsule is regular spherical and has no cracks.
[0042] Example 2
[0043] The preparation steps of 2# phase change microcapsules are as follows:
[0044] (1.1) Dissolve 1.5 g of hexadecyltrimethylammonium bromide (CTAB) in 120 g of ethanol-water solution and stir to form an aqueous phase; mix 5.5 g of n-hexadecane (n-HD) and 2.5 g of tetraethyl orthosilicate (TEOS) and stir to form an oil phase; the ethanol-water solution is prepared by mixing 32 g of CTAB and 88 g of distilled water, and the volume ratio of ethanol to water is 1:2.17.
[0045] (1.2) After the water phase and the oil phase are mixed, a dispersion homogenizer is used to homogenize and stir at a stirring speed of 9000 r / min for 5 minutes, and then ultrasonically treated for 5 minutes to complete emulsification to form an oil-in-water solution;
[0046] (1.3) Add 25 wt% ammonia water to the water-in-oil solution to make the pH of the solution reach 8.9-9.0, keep stirring, and react at 900 r / min in a 35°C water bath for 24 hours. After the reaction is completed, filter and wash the product with a 1:1 ethanol-water solution, and then dry at 40°C for 30 hours to obtain 2# phase change microcapsules.
[0047] Example 3
[0048] The preparation steps of 3# phase change microcapsules are as follows:
[0049] (1.1) Dissolve 1.5 g of hexadecyltrimethylammonium bromide (CTAB) in 135 g of ethanol-water solution and stir to form an aqueous phase; mix 5.9 g of n-hexadecane (n-HD) and 3.4 g of tetraethyl orthosilicate (TEOS) and stir to form an oil phase; the ethanol-water solution is prepared by mixing 35 g of ethanol and 100 g of distilled water, and the volume ratio of ethanol to water is 1:2.25.
[0050] (1.2) After the water phase and the oil phase are mixed, a dispersing homogenizer is used to homogenize and stir at a stirring speed of 8000 r / min for 5 minutes, and then ultrasonicated for 5 minutes to complete emulsification to form an oil-in-water solution;
[0051] (1.3) Ammonia water was added to the oil-in-water solution to make the pH value of the solution reach 9.0-9.2, and stirring was maintained. The reaction was carried out at 1000 r / min in a 40°C water bath for 20 h. After the reaction was completed, the product was filtered and washed with a 1:1 ethanol-water solution, and then dried at 60°C for 20 h to obtain 3# phase change microcapsules.
[0052] The obtained 2# and 3# phase change microcapsules have similar appearance to that of 1# phase change microcapsules.
[0053] Comparative Example 1
[0054] Preparation of 4# phase change microcapsules. This comparative example is basically the same as Example 1, except that the composition of the oil phase is different. In this comparative example, the oil phase is a mixture of 4.5g of n-hexadecane (n-HD) and 4.5g of tetraethyl orthosilicate (TEOS).
[0055] Comparative Example 2
[0056] Preparation of 5# phase change microcapsules. This comparative example is basically the same as Example 1, except that the composition of the oil phase is different. In this comparative example, the oil phase is a mixture of 6.9 g of n-hexadecane (n-HD) and 2.1 g of tetraethyl orthosilicate (TEOS).
[0057] Comparative Example 3
[0058] Preparation of 6# phase change microcapsules. This comparative example is basically the same as Example 1, except that the composition of the ethanol aqueous solution is different. In this comparative example, the ethanol aqueous solution is mixed with 23g of ethanol and 60g of distilled water, and the volume ratio of ethanol to water is 1:2.06.
[0059] Comparative Example 4
[0060] Preparation of 7# phase change microcapsules: This comparative example is basically the same as Example 1, except that the composition of the ethanol aqueous solution is different. In this comparative example, the ethanol aqueous solution is prepared by mixing 45g of ethanol and 120g of distilled water. The volume ratio of ethanol to water is 1:2.10.
[0061] Figure 2 The infrared spectra of n-HD, SiO2 and 1# phase change microcapsules are shown in Figure 1. Figure 2 n-HD@SiO2 represents 1# phase change microcapsule. In the infrared spectrum of n-HD, 2924cm -1 、2854cm -1 The absorption peak at 1463cm is the stretching vibration absorption peak of -CH2- and -CH3; -1 、720cm -1 The absorption peak at 3419cm is the bending vibration absorption peak of -CH2-. -1 The absorption peak is the -OH antisymmetric stretching vibration peak, 1632cm -1 The absorption peak at 1071 cm is the -OH bending vibration peak. -1 The absorption peak at 961cm is the symmetrical Si-O-Si antisymmetric stretching vibration absorption peak; -1 The absorption peaks at 798 cm are the bending vibration of Si-OH; -1 and 563cm -1 The absorption peak at is the stretching vibration absorption peak of Si-O. Phase change microcapsule 1# contains all the characteristic absorption peaks of SiO2 synthesized by the hydrolysis of phase change material n-HD and TEOS, which proves the successful synthesis of phase change microcapsule.
[0062] The amount of phase change material contained in the phase change microcapsule is characterized by the weight loss rate. The higher the content, the higher the phase change material contained. When testing the weight loss rate, the phase change microcapsule is first placed in a 60°C oven and treated at a constant temperature for 6 hours to remove the moisture on the surface of the microcapsule and the core material remaining in the broken microcapsule. Then 0.5g of the phase change microcapsule is placed in a crucible, the shell of the microcapsule is destroyed to expose the core material, and it is placed in a box-type experimental electric furnace and burned at 300°C for 2 hours to remove the core material in the microcapsule and the organic matter on the shell of the microcapsule. The remaining is the shell. The 1-7# phase change microcapsules are tested separately, and the weight loss rates from 1# phase change microcapsule to 7# phase change microcapsule are 78.9%, 78.8%, 78.5%, 69.9%, 50.1%, 45.4%, and 65%, respectively. The above data indicate that the appropriate mass ratio of n-hexadecane to tetraethyl orthosilicate, and the mass ratio of the oil phase to the water in the ethanol aqueous solution can effectively improve the quality of the phase change microcapsules.
[0063] Implementation 4
[0064] The preparation steps of 1# coating are as follows:
[0065] (1) Phase change microcapsules #1 coated with phase change materials were uniformly dispersed in a Tris-HCl buffer solution with a pH of 8.1, and continuously ultrasonicated for 2 h at room temperature to form a capsule buffer solution. The concentration of the phase change microcapsules in the buffer solution was 5 g / L.
[0066] (2) Take 100 mL of capsule buffer, add 0.14 g dopamine, 1.4 g carboxybetaine acrylamide, 0.71 g copper sulfate and 0.56 g hydrogen peroxide into the capsule buffer, stir at 180 r / min, react at 20°C, and react for 2.5 h. After the reaction is completed, filter, wash with deionized water, and dry at 60°C for 12 h to obtain 1# double-shell microcapsules. Hydrogen peroxide is calculated as pure H2O2.
[0067] (3) 1 g of 1# double-shell microcapsules was placed in 100 g of a 10% polyvinyl pyrrolidone aqueous solution containing 0.5 wt % of a fumed silica anti-settling agent and 0.1 wt % of an aqueous silicone defoaming agent to form a 1# coating.
[0068] Example 5
[0069] The preparation steps of 2# coating are as follows:
[0070] (1) Phase change microcapsules No. 1 coated with phase change material were uniformly dispersed in a Tris-HCl buffer solution with a pH of 8.5, and continuously ultrasonicated for 2 h at room temperature to form a capsule buffer solution. The concentration of the phase change microcapsules in the buffer solution was 8 g / L.
[0071] (2) Take 100 mL of capsule buffer, add 0.18 g of dopamine, 2.7 g of carboxybetaine acrylamide, 0.54 g of copper sulfate and 0.62 g of hydrogen peroxide into the capsule buffer, stir at 200 r / min, react at 25°C, and react for 1.5 h. After the reaction is completed, filter, wash with deionized water, and dry at 60°C for 12 h to obtain 2# double-shell microcapsules. Hydrogen peroxide is calculated as pure H2O2.
[0072] (3) 1.6 g of 2# double-shell microcapsules were placed in 100 g of a 13% polyvinyl pyrrolidone aqueous solution, wherein the polyvinyl pyrrolidone aqueous solution contained 1.2 wt % of a fumed silica anti-settling agent and 0.3 wt % of an aqueous silicone defoaming agent to form a 2# coating.
[0073] Example 6
[0074] The preparation steps of 3# coating are as follows:
[0075] (1) The 1# phase change microcapsules coated with phase change material were uniformly dispersed in a Tris-HCl buffer solution with a pH of 8.8, and continuously ultrasonicated for 2 h at room temperature to form a capsule buffer solution. The concentration of the phase change microcapsules in the buffer solution was 10 g / L.
[0076] (2) Take 100 mL of capsule buffer, add 0.19 g dopamine, 1.52 g carboxybetaine acrylamide, 1.1 g copper sulfate and 0.57 g hydrogen peroxide into the capsule buffer, stir at 300 r / min, react at 30°C, and react for 0.8 h. After the reaction is completed, filter, wash with deionized water, and dry at 60°C for 12 h to obtain 3# double-shell microcapsules. Hydrogen peroxide is calculated as pure H2O2.
[0077] (3) 0.55 g of 3# double-shell microcapsules were placed in 100 g of 8% polyvinyl pyrrolidone aqueous solution, wherein the polyvinyl pyrrolidone aqueous solution contained 2 wt % of fumed silica anti-settling agent and 0.5 wt % of aqueous organosilicon defoaming agent to form 3# coating.
[0078] Comparative Example 5
[0079] Preparation of 4# double-shell microcapsules: The preparation of 4# double-shell microcapsules is basically the same as that of 1# double-shell microcapsules, except that carboxybetaine acrylamide is eliminated.
[0080] 1g of 4# double-shell microcapsules was placed in 100g of a 10% polyvinyl pyrrolidone aqueous solution, wherein the polyvinyl pyrrolidone aqueous solution contained 0.5wt% of a fumed silica anti-settling agent and 0.1wt% of an aqueous silicone defoaming agent to form a 4# coating.
[0081] Comparative Example 6
[0082] The preparation steps of 5# coating are as follows:
[0083] 1g of 1# phase change microcapsules was placed in 100g of a 10% polyvinyl pyrrolidone aqueous solution, wherein the polyvinyl pyrrolidone aqueous solution contained 0.5wt% of a fumed silica anti-settling agent and 0.1wt% of an aqueous silicone defoaming agent to form a 5# coating.
[0084] Comparative Example 7
[0085] Preparation of 6# double-shell microcapsules: The preparation of 6# double-shell microcapsules is basically the same as that of 1# double-shell microcapsules, except that the added amount of carboxybetaine acrylamide is 0.7 g.
[0086] 1g of 6# double-shell microcapsules was placed in 100g of a 10% polyvinyl pyrrolidone aqueous solution, wherein the polyvinyl pyrrolidone aqueous solution contained 0.5wt% of a fumed silica anti-settling agent and 0.1wt% of an aqueous silicone defoaming agent to form a 6# coating.
[0087] Comparative Example 8
[0088] Preparation of 7# double-shell microcapsules: The preparation of 7# double-shell microcapsules is basically the same as that of 1# double-shell microcapsules, except that the added amount of carboxybetaine acrylamide is 2.8 g.
[0089] 1g of 7# double-shell microcapsules was placed in 100g of a 10% polyvinyl pyrrolidone aqueous solution, wherein the polyvinyl pyrrolidone aqueous solution contained 0.5wt% of a fumed silica anti-settling agent and 0.1wt% of an aqueous silicone defoaming agent to form a 7# coating.
[0090] The SEM images and infrared spectra of 1# phase change microcapsule, 1# double-shell microcapsule and 4# double-shell microcapsule are listed in Figure 3 and Figure 4 , Figure 3 middle, Figure 3 (a) is the SEM image of 1# phase change microcapsule. Figure 3 (b) is the SEM image of 4# double-shell microcapsule. Figure 3 (c) is the SEM image of 1# double-shell microcapsule. Figure 4 In the figure, n-HD@SiO2 represents 1# phase change microcapsule, n-HD@SiO2@PDA represents 4# double-shell microcapsule, and n-HD@SiO2@PDA / PCBAA-10 represents 1# double-shell microcapsule.
[0091] from Figure 3From the SEM images, it can be seen that all microcapsules are in regular spherical shapes. The appearance of the 1# phase change microcapsule is the white color of silica. DA is oxidatively polymerized to produce black PDA. The black color on the surface of the 4# double-shell microcapsule confirms that PDA is successfully deposited on the surface of the microcapsule. The color of the 1# double-shell microcapsule is brown, which is yellower than the color of the surface of the 4# double-shell microcapsule. This is mainly because DA undergoes self-oxidation to form semiquinone free radicals to initiate the polymerization of the monomer CBAA, which is co-deposited on the surface of the phase change microcapsule. The surface of the 1# double-shell microcapsule is mainly composed of PDA as the middle layer, and the outer surface is a polymerized long-chain PCBAA brush, and the color of PCBAA is yellow.
[0092] from Figure 4 It can be seen that in the spectrum of phase change microcapsule 1#, 2927cm -1 、2855cm -1 The absorption peak at 1627cm is the stretching vibration absorption peak of -CH2- and -CH3; -1 The absorption peak at 1377 cm is the -OH bending vibration peak. -1 The absorption peak CH is the bending (in-plane) stretching vibration absorption peak; 1231cm -1 The absorption peak at 1078cm is the CC stretching vibration absorption peak; -1 The absorption peak at 1464cm is the symmetrical Si-O-Si antisymmetric stretching vibration absorption peak; -1 、720cm -1 The absorption peak at 960cm is the bending vibration absorption peak of -CH2-; -1 The absorption peaks at 794cm are the bending vibration of Si-OH; -1 and 564cm -1 The absorption peak at 1610cm is the stretching vibration absorption peak of Si-O. -1 and 1510cm -1 The absorption peaks at 1630cm are the stretching vibration absorption peaks of C=C and C=N in PDA. -1 and 1330cm -1 The absorption peaks at 1246cm are the stretching vibration absorption peaks of the amide I band and amide II band of -CONH-; -1 The absorption peak at is the CN stretching vibration absorption peak. Figure 4 It can be seen that the infrared spectra of 1# double-shell microcapsules and 4# double-shell microcapsules are not significantly different from the spectrum of unmodified 1# phase change microcapsules, which may be due to the overlap of the characteristic absorption peaks of PDA and PCBAA with the infrared absorption peak of 1# phase change microcapsules.
[0093] In order to verify that PCBAA and PDA were successfully co-deposited on the surface of phase change microcapsules, the surface chemical compositions of 1# double-shell microcapsules and 4# double-shell microcapsules were characterized by X-ray photoelectron spectroscopy (XPS). Figure 5 shown.
[0094] Figure 5 In the figure, n-HD@SiO2@PDA represents 4# double-shell microcapsule, n-HD@SiO2@PDA / PCBAA-10 represents 1# double-shell microcapsule, Figure 5 (a) is the comparison of XPS spectra of C1s core level spectra of 1# double-shell microcapsule and 4# double-shell microcapsule. Figure 5 (b) is the C1s core-level spectrum of 4# double-shell microcapsule. Figure 5 (c) C1s core-level spectrum of 1# double-shell microcapsule.
[0095] Since both 1# double-shell microcapsules and 4# double-shell microcapsules contain elements such as C, N, and O, the comparison of the C1s core-level spectra of 1# double-shell microcapsules and 4# double-shell microcapsules is shown in Figure 2. Figure 5 As shown in (a), the appearance of the OC=O peak at 288.1eV indicates that PCBAA and PDA are co-deposited on the surface of the phase change microcapsules. In order to confirm this inference, the peaks of the C element of the 1# double-shell microcapsules and the 4# double-shell microcapsules were fitted, and the combination state of the C element was analyzed. Figure 5 (b) shows the C1s peak of 4# double-shell microcapsule, and the peaks at 284.3, 284.8, 286.1 and 287.0 eV belong to CN, CC / CH, CO and C=N / C=O, respectively. Compared with the C1s peak of 4# double-shell microcapsule, the appearance of OC=O peak at 288.1 eV in the C1s core-level spectrum of 1# double-shell microcapsule indicates that PCBAA and PDA are successfully deposited on the surface of phase change microcapsules.
[0096] The photothermal conversion efficiency of 1# phase change microcapsule, 1# double-shell microcapsule, 2# double-shell microcapsule, 4# double-shell microcapsule and 7# double-shell microcapsule was tested.
[0097] The photothermal conversion experiment was conducted using an infrared light source to simulate sunlight and study the photothermal conversion performance of different phase change microcapsules. The temperature-time curve of equal amounts of microcapsules under a constant power infrared light was recorded in real time by a thermal imager to obtain Figure 6 , Figure 6In the figure, n-HD@SiO2 represents 1# phase change microcapsule, n-HD@SiO2@PDA represents 4# double-shell microcapsule, n-HD@SiO2@PDA / PCBAA-10 represents 1# double-shell microcapsule, n-HD@SiO2@PDA / PCBAA-15 represents 2# double-shell microcapsule, and n-HD@SiO2@PDA / PCBAA-20 represents 7# double-shell microcapsule.
[0098] Taking the temperature-time curve of the unmodified 1# phase-change microcapsule as the control group, it can be seen that the photothermal conversion performance of the phase-change microcapsules modified by PDA is better than that of the control group, and with the increase of CBAA feed, the photothermal conversion effect of the corresponding modified microcapsules has a downward trend. Among them, the photothermal conversion effect of the 4# double-shell microcapsule is the best, and the maximum temperature can reach 61.1℃, which is 12.2℃ higher than the control group. This is because a large amount of PDA is deposited on the surface of the phase-change microcapsule. PDA contains a large number of benzene rings and indole groups, and has a strong absorption capacity for sunlight. Therefore, the modified microcapsule has an excellent photothermal conversion effect and can quickly and efficiently convert solar energy into thermal energy. The 1# phase-change microcapsule in the control group reached a maximum temperature of 49°C at 470s, while the modified phase-change microcapsules could quickly heat up to the maximum temperature of the 1# phase-change microcapsule in about 36s. The maximum temperature of the 1# double-shell microcapsule could reach 58.8°C, and the heating rate was comparable to that of the 4# double-shell microcapsule. The performance of the 2# double-shell microcapsule was similar to that of the 1# double-shell microcapsule, but the photothermal conversion performance of the 7# double-shell microcapsule was relatively reduced.
[0099] The static contact angles of 1#-7# coatings were tested. The contact angle test method was: measured using a contact angle meter. The liquid used in the test was distilled water. The droplet size was 4 microliters. Each sample was measured three times, and the average value was taken as the final contact angle of the coating. The results showed that the surface modification of the microcapsules improved the hydrophilicity of the microcapsule surface to a certain extent. The contact angle of the coating surface of 1# coating was 7.8°, the contact angle of the coating surface of 2# coating was 8.8°, the contact angle of the coating surface of 3# coating was 8.3°, the contact angle of the coating surface of 4# coating was 11.2°, the contact angle of the coating surface of 5# coating was 13.7°, the contact angle of the coating surface of 6# coating was 10.3°, the contact angle of the coating surface of 7# coating was 10.8°, and the contact angle of the coating surface of 8# coating was 10.2°. The above situation shows that the appropriate proportion of DA and CB AA can effectively reduce the contact angle of the coating, but as the proportion of CBAA increases, the contact angle of the coating surface first decreases and then increases. This is because when CBAA is initially added, the water absorption capacity of PCBAA can be used to lock non-freezing water until the optimal ratio is reached. However, as the proportion of CBAA continues to increase, the intramolecular dipole-dipole interaction between its zwitterionic monomers leads to self-association, and the brush layer is in a super-collapsed state. In this super-collapsed state, the polyzwitterionic layer contains much less water than the non-associated state. The contact angles of the coating surface containing CBAA are all lower than those of the PDA coating, so the hydrophilicity of the coating also indirectly proves that the one-step co-deposition technology can fix the polymerized PCBAA on the phase change microcapsules through PDA.
[0100] The anti-icing ability of each coating is tested using a self-made anti-icing tester. Please refer to Figure 7 The anti-icing detector includes a freezing box and a box cover covering the freezing box, a detection cavity is formed between the box cover and the freezing box, the top plate of the freezing box is formed as a freezing platform, a semiconductor refrigeration plate is installed under the top plate, a coated glass slide is placed on the freezing platform, a rubber ring is fixed on the coated glass slide during detection, a certain amount of distilled water is added to the rubber ring, and the platform temperature is cooled from 10°C to -18°C by using the semiconductor refrigeration plate, when the freezing platform reaches the specified temperature, the timing starts, and the time until the distilled water is completely frozen is defined as the freezing delay time of the coating. Figure 7 In the figure, the blue part is the freezing platform, and the white part on the freezing platform is the coated slide.
[0101] Taking pure PVP coating as the benchmark, at -18℃, the freezing time of pure PVP coating is 63s, the freezing delay time of 1# coating is delayed by 127.3s to 190.3s, the freezing delay time of 2# coating is delayed by 110.8s, the freezing delay time of 3# coating is delayed by 95.8s, the freezing delay time of 4# coating is delayed by 19.4s, the freezing delay time of 5# coating is delayed by 10s, the freezing delay time of 6# coating is delayed by 28.4s, the freezing delay time of 7# coating is delayed by 30.2s, and the freezing delay time of 8# coating is delayed by 35.8s.
[0102] The above data show that the hydrophilic groups contained in the zwitterionic polymer PCBAA can interact strongly with water molecules, so that the formed hydration layer can still exist stably at low temperatures. The hydration layer can act as a lubricant between the ice and the substrate surface, thereby reducing the adhesion between the ice and the surface.
[0103] The freezing delay time of 1# coating was tested at -15℃ and -21℃. The results showed that the freezing delay time of 1# coating was 342.3s at -15℃ and 74.7s at -21℃, indicating that 1# coating has good anti-icing performance at low temperatures.
Claims
1. A method for preparing a coating having both anti-icing and photothermal conversion properties, characterized in that: The steps include: (1) uniformly dispersing the phase change microcapsules coated with the phase change material in a Tris-HCl buffer solution to form a capsule buffer solution; (2) adding dopamine, carboxybetaine acrylamide, copper sulfate and hydrogen peroxide to the capsule buffer, stirring and reacting, and after the reaction is completed, filtering, washing and drying to obtain double-shell microcapsules; The mass ratio of phase change microcapsules, dopamine, carboxybetaine acrylamide, copper sulfate and hydrogen peroxide is (3.5-5.5):1:(8-15):(3-6):(3-4), wherein the hydrogen peroxide is calculated as pure H2O2; (3) placing the double-shell microcapsules in a polyvinyl pyrrolidone aqueous solution containing an anti-settling agent and a defoaming agent to form a coating; Phase change microcapsules are prepared by the following steps: (1.1) Hexadecyltrimethylammonium bromide is dissolved in an ethanol aqueous solution and stirred to form an aqueous phase; n-hexadecane and tetraethyl orthosilicate are mixed and stirred to form an oil phase; (1.2) mixing, stirring and emulsifying the water phase and the oil phase to form an oil-in-water solution; (1.3) adding aqueous ammonia to the oil-in-water solution to adjust the pH value of the solution to 8.8-9.2, maintaining stirring to carry out the reaction, filtering after the reaction is completed, washing and drying the product to obtain phase change microcapsules; The mass ratio of the oil phase to the water in the ethanol aqueous solution is 1:(9-11), the mass ratio of hexadecyltrimethylammonium bromide to the ethanol aqueous solution is 1:(80-90), and the volume ratio of ethanol to water in the ethanol aqueous solution is 1:(2-3).
2. The preparation method according to claim 1, characterized in that: In step (1), the pH of the Tris-HCl buffer solution is 8-8.8, and the concentration of the phase change microcapsules in the Tris-HCl buffer solution is 5-10 g / L.
3. The preparation method according to claim 1, characterized in that: In step (2), the reaction temperature is 20-30°C, the reaction time is 0.8-2.5h, and the stirring speed is 150-300r / min.
4. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of double-shell microcapsules to polyvinyl pyrrolidone is 1:(8-15), the concentration of the polyvinyl pyrrolidone aqueous solution is 8-13wt%; the polyvinyl pyrrolidone aqueous solution contains 0.5-2wt% of an anti-settling agent and 0.1-0.5wt% of a defoaming agent, wherein the anti-settling agent is fumed silica and the defoaming agent is a water-based silicone defoaming agent.
5. The preparation method according to claim 1, characterized in that: In step (1.1), the mass ratio of n-hexadecane to tetraethyl orthosilicate is 10:(4-7).
6. The preparation method according to claim 1, characterized in that: In step (1.3), the reaction time is 20-30 h and the reaction temperature is 30-40 °C.
7. A coating having both anti-icing and light-to-heat conversion properties, characterized in that: The preparation method is described in any one of claims 1 to 6.
Citation Information
Patent Citations
Super-hydrophilic / underwater super-oleophobic co-deposition coating and preparation method thereof
CN110433530A
Phase-change micro-capsule with full-wave-band photo-thermal conversion function and preparation method thereof
CN112251197A
Self-regulating photo-thermal anti-icing and deicing coating and coating
CN115873490A
Cited By
Anti-icing diversion coating capable of being rapidly cured on surface of power transmission line and preparation method of anti-icing diversion coating
CN122563422A